The Relationship between the Use of Social Media and Creativity and the Sustainability of the Chili Cracker MSME Business in Dumai City - Intan Afriyani Aisyah; Sumarno Sumarno; M. Yogi Riyantama Isjoni (CV. Rayyan Dwi Bharata, 2024)
This research aims to find out (1) how the use of social media is related to the sustainability of the chili crackers MSME business in Dumai City. (2) and what is the relationship between creativity and the sustainability of the chili cracker UMKM business in Dumai City. This research is included in quantitative research. The population in this study were 20 Chili Cracker MSME businesses in Dumai City with a research sample of 15 Chili Cracker MSME businesses in Dumai City. The sampling technique is saturated sampling. The data collection techniques used were interviews, questionnaires and documentation. This research uses descriptive analysis techniques, normality tests and Spearman rank correlation statistical tests. The results of this research show (1) the use of social media has a positive and significant relationship with the sustainability of the chili cracker MSME business in Dumai City. (2) creativity has a positive and significant relationship with the sustainability of the chili cracker MSME business in Dumai City.